z+26=2z

Simple and best practice solution for z+26=2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z+26=2z equation:


Simplifying
z + 26 = 2z

Reorder the terms:
26 + z = 2z

Solving
26 + z = 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
26 + z + -2z = 2z + -2z

Combine like terms: z + -2z = -1z
26 + -1z = 2z + -2z

Combine like terms: 2z + -2z = 0
26 + -1z = 0

Add '-26' to each side of the equation.
26 + -26 + -1z = 0 + -26

Combine like terms: 26 + -26 = 0
0 + -1z = 0 + -26
-1z = 0 + -26

Combine like terms: 0 + -26 = -26
-1z = -26

Divide each side by '-1'.
z = 26

Simplifying
z = 26

See similar equations:

| 8x-10=18-6x | | 10=m-(-17) | | a+51=4a | | f(2)=2 | | 5a^2+20a-60=0 | | 2/3x+4=1/2+5 | | 17-9y=8+16y | | 4x+3=9x-47 | | 3x-140+x-18=180 | | u+46=3u | | 1/3x=6-(1/5x) | | 1/3x=6-,1/5x | | m-41=12 | | 5x-5.6=1.3 | | 3x+2x+5=180 | | -18+b=4 | | 3(q-2)+5q-7=2q | | 9p+3p^2=30 | | y=3x^3-2x^2 | | Y=2x^2+4x+8 | | 10-2t=-6t+10 | | 6x+5=x-14 | | (8+u)(4u+1)=0 | | x^2+12ax+35a^2=0 | | X^2+6x+43=0 | | 68=6x+6x+8 | | 9x-8=2x+34 | | -2z^2+5z+3=0 | | 3(y-5)+1=2y+34-2y | | -5x-3y-5x-8y= | | -43=-61+x | | 4ay/3d |

Equations solver categories